NOKIA PHONE APPLICATION TREATMENT USING MACROMEDIA DREAMWEAVER MX - Taufik Zulfika; Yudi Irawan Chandra.,SKom.,MMSI (Jurnal Sistem Informasi, 2009)
Nokia Care application program has been designed using Macromedia DreamweaverMX program whose purpose is to make the program a web application that displaysvarious information about Nokia care accessible to the people, so that mobile phoneusers know better.Use Table, Link and others in making this program a facility has been provided byMacromedia Dreamweaver MX to facilitate the creation in making a web page.